Sociocognitive Analysis of Facebook Memes: Investigating Political Ideologies and Identity Formation among Pakistani Youth - Sana Tafseer; Farah Arshad; Husna Khalid; Dr. Jahanzeb Jahan (Dialogue Social Science Review (DSSR), 2025)
The transformational significance of Facebook memes as a digital communication tool that is changing political discourse among Pakistani youth is examined in this research. With Teun A. van Dijk's Socio-Cognitive Theory as its analytical framework, the study explores how political memes, with special emphasis to how they depict political people, reflect power relations, embody complex meanings, and function as tools of resistance. 16 political memes that were randomly chosen from highly engaged Facebook pages representing a range of political themes were analyzed using a qualitative technique. The research looks at the mental processes that these visual artifacts use to build ideological alignments, affect political views, and help young people develop their identities. The results demonstrate the dual role of memes as both accelerators for ideological change and mirrors of social power systems. The research demonstrates how memes not only reflect dominant political beliefs but also promote changes in political attitudes and actions by examining the relationship between digital media, politics, and identity. By showing how meme-based communication promotes ideological development and is crucial in forming the political awareness of Pakistan's younger generations, this study advances our understanding of the role of digital platforms in modern political involvement.